Heterogeneous Enantioselective Hydrogenation Theory and Practice - Klabunovskii, Evgenii; Smith, Gerard V.; Zsigmond, Ágnes; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2006)
Heterogeneous Enantioselective Hydrogenation: Theory and Practice reviews the development of enantioselective hydrogenation reaction catalysts. The book looks at the first relatively ineffective catalysts right through to modern highly effective enantioselective catalytic systems, comparable in their efficiency to chiral metal complexes and enzymatic systems. The book begins with a summary of the first work on heterogeneous metal catalysts, which showed only the principal possibilities of enantioselective reactions. The book then elaborates on metal catalysts which have enantioselectivities close to 100%. Finally, the book describes the practical utilization of chiral catalytic systems in processes of hydrogenation. The a - and b -hydroxy carboxylic acid esters produced are precursors for manufacturing many synthones used for medicines as well as for monomers used for biodegradable polyesters, both of which have important practical applications. The book summarizes more than 800 scientific papers in the field of enantioselective catalytic hydrogenation reactions, mainly those using heterogeneous metal catalysts. It provides detailed explanations of special techniques for the preparation of effective dissymmetric catalysts which provide highly efficient catalytic systems. This book differs from previous publications by virtue of the recommendations for the practical utilization of recently described preparations of metal catalysts. Heterogeneous Enantioselective Hydrogenation: Theory and Practice will be an invaluable resource to catalysis researchers as well as to those utilizing the technology.
Preface. Asymmetric adsorption on minerals -- Introduction -- Attempts of asymmetric adsorption on clays -- Asymmetric adsorption on quartz crystals -- Imprinting chiral adsorbents: specifically modified silica gels -- Heterogeneous hydrogenation catalysts based on quartz: General -- Asymmetric hydrogenation on metal-quartz catalysts -- General comments on adsorption and catalysis using quartz-crystals -- On the mechanism of 'Quartz –catalysis -- Evaluation of absolute configurations on data from 'Quartz-catalysis -- Heterogeneous catalysts supported on chiral carriers -- Pd-silica catalysts -- Metal colloids as asymmetric catalysts -- Asymmetric template catalysis -- Metal catalysts supported on polymers -- Hydrogenation on catalysts based on Ni and bimetals: Background and elaboration of Ni catalysts modified with amino- and hydroxy acids -- Preparation variables for new nickel catalysts modified with tartaric acid -- Bimetallic and multimetallic modified hydrogenation catalysts -- Modified nickel and bimetallic catalysts -- Mechanism of enantioselective hydrogenation -- Asymmetric hydrogenation of 2-oxocarboxylic acid esters and unsaturated carboxylic acids on modified Pt and Pd catalysts: General -- Properties of catalysts -- Structure of the modifiers -- Structure of substrate -- Effects of solvents and additives -- Reaction variables -- On the mechanism of hydrogenation -- Conclusions -- Electrochemical enantioselective reduction: Abstract.-General -- Practical asymmetric catalytic reactions -- Asymmetric metal complex catalysts in industry -- Heterogenized metal complex catalysts -- Asymmetric hydrogenation of alpha-keto esters on chiral metal complexes -- Catalytic synthesis of pantolactone and other pharmaceuticals - using chiral homogeneous metal complexes -- References.
Keywords: Organic chemistry; Catalysis; Organometallic chemistry .; Materials—Surfaces.; Thin films; Chemical engineering; Evolutionary biology; Organic Chemistry; Catalysis; Organometallic Chemistry; Surfaces and Interfaces, Thin Films; Industrial Chemistry/Chemical Engineering; Evolutionary Biology